2008
DOI: 10.1111/j.1472-765x.2007.02310.x
|View full text |Cite
|
Sign up to set email alerts
|

DNase test as a novel approach for the routine screening of Corynebacterium diphtheriae

Abstract: Aims:  To examine the value of the DNase test as an alternative procedure for differentiating Corynebacterium diphtheriae from Corynebacterium‐like colonies. Methods and Results:  DNase test medium was inoculated by spotting a loopful of bacterial growth and incubated aerobically at 37°C. The DNase production was detectable following both 24 and 48 h incubation periods. The DNase activity was detected in all 91 C. diphtheriae (37 toxigenic and 54 nontoxigenic) strains examined, previously identified by both co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 17 publications
(27 reference statements)
1
15
0
1
Order By: Relevance
“…As alternative screening test for differentiating C. diphtheriae from Corynebacterium-like colonies the DNAse test was proposed (Pimenta et al 2008b). After incubation of colonies inoculated on DNAse-test media for 24 to 48 h, all 91 tested C. diphtheriae isolates (toxigenic and non-toxigenic) showed DNAse activity, while 93.9 % of 564 nondiphtherial Corynebacterium strains (including 3 C. pseudotuberculosis isolates) yielded negative results.…”
Section: Presumptive Identification Of Potentially Toxigenicmentioning
confidence: 99%
“…As alternative screening test for differentiating C. diphtheriae from Corynebacterium-like colonies the DNAse test was proposed (Pimenta et al 2008b). After incubation of colonies inoculated on DNAse-test media for 24 to 48 h, all 91 tested C. diphtheriae isolates (toxigenic and non-toxigenic) showed DNAse activity, while 93.9 % of 564 nondiphtherial Corynebacterium strains (including 3 C. pseudotuberculosis isolates) yielded negative results.…”
Section: Presumptive Identification Of Potentially Toxigenicmentioning
confidence: 99%
“…Other clinical specimens were inoculated onto a Columbia agar base with the addition of 5% sheep's blood and incubated at 37ºC in a 3-5% CO 2 atmosphere and monitored for 72 h (Camello et al 2003). Positive bacterial cultures for irregular Gram-positive rods were preliminarily characterised by colonial morphology, pigmentation, haemolysis, DNase activity and CAMP reaction with Staphylococcus aureus (Camello et al 2003, Funke & Bernard 2007, Pimenta et al 2008. Phenotypic characterisation was also performed using the semi-automated API Coryne System 3.0 (bioMérieux) with the API web decoding system (apiweb.biomerieux.com) (Almuzara et al 2006, Funke & Bernard 2007, Campanile et al 2009).…”
Section: Subjects Materials and Methodsmentioning
confidence: 99%
“…and M. catarrhalis (Elston and Elston, 1968;Fusillo and Weiss, 1959;MacFaddin, 2000). A short set of routine tests, which includes DNase as a major differentiating factor, would be especially useful as a screening of microorganisms including Corynebacterium species (Pimenta et al, 2008). We showed that it is possible to differentiate S. marcescens from E. aerogenes in as short as half an hour using the DTT.…”
Section: Discussionmentioning
confidence: 95%
“…The major drawback of these tests in addition to problems mentioned is the necessity of a long time to see the results of DNase activity of the bacteria. Defi ning the DNase activity of S. aureus or Corynebacterium takes 24 to 48 h using the DNase agar test (Pimenta et al, 2008). Here we developed a simple, rapid and inexpensive method to illustrate DNase activity of any microorganism that can grow in any broth medium.…”
mentioning
confidence: 99%